A Decaheme Cytochrome as a Molecular Electron Conduit in Dye‐Sensitized Photoanodes. (11th March 2015) - Hwang, Ee Taek; Sheikh, Khizar; Orchard, Katherine L.; Hojo, Daisuke; Radu, Valentin; Lee, Chong‐Yong; Ainsworth, Emma; Lockwood, Colin; Gross, Manuela A.; Adschiri, Tadafumi; Reisner, Erwin; Butt, Julea N.; et al.
Abstract : In nature, charge recombination in light‐harvesting reaction centers is minimized by efficient charge separation. Here, it is aimed to mimic this by coupling dye‐sensitized TiO2 nanocrystals to a decaheme protein, MtrC from Shewanella oneidensis MR‐1, where the 10 hemes of MtrC form a ≈7‐nm‐long molecular wire between the TiO2 and the underlying electrode. The system is assembled by forming a densely packed MtrC film on an ultra‐flat gold electrode, followed by the adsorption of approximately 7 nm TiO2 nanocrystals that are modified with a phosphonated bipyridine Ru(II) dye (RuP). The step‐by‐step construction of the MtrC/TiO2 system is monitored with (photo)electrochemistry, quartz‐crystal microbalance with dissipation (QCM‐D), and atomic force microscopy (AFM). Photocurrents are dependent on the redox state of the MtrC, confirming that electrons are transferred from the TiO2 nanocrystals to the surface via the MtrC conduit. In other words, in these TiO2 /MtrC hybrid photodiodes, MtrC traps the conduction‐band electrons from TiO2 before transferring them to the electrode, creating a photobioelectrochemical system in which a redox protein is used to mimic the efficient charge separation found in biological photosystems. Abstract : A molecular electron conduit of the decaheme cytochrome, MtrC, interfacing dye‐sensitized TiO2 nanocrystals to an electrode support is assembled and demonstrated. The constructed layers of MtrC and TiO2 nanocrystals photosensitized with RuP are used in a biomimetic hybrid photobiochemical system with the aim to mimic the efficient spatial charge separation found in biological photosystems.